LEGALITY OF CREATING AI-BASED CLUSTERED BATIK DESIGN PROTOTYPES - Purwaningsih, Endang; Muslikh, Muslikh; Fathurahman, Muhamad; Basrowi, Basrowi (Universitas Galuh, 2025)
This research examines the legality of applying artificial intelligence (AI) to product innovations by research partners, produced and protected by intellectual property rights (IPR), including industrial design, trademarks, and copyrights. The role of the batik association is to produce prototypes in the form of batik industry innovations per cluster while still incorporating a touch of human art, ensuring that each cluster maintains its uniqueness according to traditional standards and does not violate IPR. This new design is copyrighted, registered as an industrial design and trademark, and then produced by partners. The issues discussed in this research are: (1) The form of legal protection given to AI-based products, and the role of partners in clusters in protecting and preserving batik.The methods used include a participatory research approach, sociological approach, and statute approach, using a mixed method that collaborates qualitative and quantitative methods. The research results show that: (1) The form of legal protection for AI-based products expected by the partners includes protection accompanied by promotion, as well as legal assistance and facilitation of legality, whether in the form of trademarks, copyrights, or industrial designs. From a legal perspective, the new motif, which contains art, can be copyrighted, commercialized under a trademark, and the innovation of batik motifs that uphold traditional standards is accommodated in AI-based innovations because the AI modeling is done based on input data of batik motifs per cluster according to their respective areas, ensuring that traditional standards are maintained. (2) The role of partners in clusters in protecting and preserving batik, through associations, facilitates and streamlines batik preservation, channels government programs and other stakeholders' assistance, as well as promotion, and preserves traditional batik standards according to local wisdom.